2017
DOI: 10.1111/chd.12485
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in perioperative care in pediatric cardiac surgery by shifting the primary focus of treatment from cardiac output to perfusion pressure: Are beta stimulants still needed?

Abstract: Objective: An important aspect of perioperative care in pediatric cardiac surgery is maintenance of optimal hemodynamic status using vasoactive/inotropic agents. Conventionally, this has focused on maintenance of cardiac output rather than perfusion pressure. However, this approach has been abandoned in our center in favor of one focusing primarily on perfusion pressure, which is presented here and compared to the conventional approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Through comparion of two groups of open and closed heart surgery, significant association was found during twice after surgery, hence frequency of hypomagnesaemia in patients who had undergone closed surgery was higher at first hour after operation while no significant relationship was observed between two groups on second day and interestingly hypomagnesaemia was significantly higher in open surgery group. Bearing in mind that the sole perioperative recommended magnesium was through cardioplegia solution, this is important particularly in comparing with other researches 7,8. Therefore, it could be concluded that some other pre and post-operative metabolic issues in addition to cardiopulmonary bypass should be involved in postoperative hypomagnesaemia.…”
Section: Discussionmentioning
confidence: 95%
“…Through comparion of two groups of open and closed heart surgery, significant association was found during twice after surgery, hence frequency of hypomagnesaemia in patients who had undergone closed surgery was higher at first hour after operation while no significant relationship was observed between two groups on second day and interestingly hypomagnesaemia was significantly higher in open surgery group. Bearing in mind that the sole perioperative recommended magnesium was through cardioplegia solution, this is important particularly in comparing with other researches 7,8. Therefore, it could be concluded that some other pre and post-operative metabolic issues in addition to cardiopulmonary bypass should be involved in postoperative hypomagnesaemia.…”
Section: Discussionmentioning
confidence: 95%
“…30 Optimising perfusion pressure instead of focusing on maximising CO, by favouring low-dose dopamine agonists and lusitropic agents (milrinone) has been shown to improve mortality and reduce ventilation times in paediatric cardiac surgery patients. 31 Fenestration improves CO at times of high PVR by allowing diversion of blood from the "bottle-neck" of the circuit to the heart. 30 More research into short-term benefits of fenestration is needed as whilst it also reduces PAP and reduces the risk of PPE, a recent meta-analysis suggests no significant difference in intrahospital mortality and LOS compared to nonfenestrated patients.…”
Section: Circulationmentioning
confidence: 99%
“…The quality of evidence (GRADE) was very low (three studies included and evaluated this outcome among the eight and high risk of bias). II°) Perioperative lactate levels: 9 studies in cardiac surgery were included for meta-analysis (6 observational prospective and 3 observational retrospective) [19][20][21][22][23][24][30][31][32]. II.1°) Mortality (Supplemental Figure 7): 9 trials (6 prospective and 3 retrospective) with 1690 children in cardiac surgery were included for this outcome.…”
Section: Effects Of Interventions I°)mentioning
confidence: 99%